(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article discusses the concept, as well as the main issues of the personnel reserve system for the civil service. According to the author, the right approach to the formation of a personnel reserve will help ensure the continuity of management, and, consequently, the effective operation of government bodies. Also, within the framework of the study, some aspects of the formation of a successful, strong personnel reserve in the civil service were analyzed.